Staple Food Prices in Sub-Saharan Africa : An Empirical Assessment - Okou, Cedric (IMF Working Papers; Working Paper ;, 2022)
This paper analyzes the domestic and external drivers of local staple food prices in Sub-Saharan Africa. Using data on domestic market prices of the five most consumed staple foods from 15 countries, this paper finds that external factors drive food price inflation, but domestic factors can mitigate these vulnerabilities. On the external side, our estimations show that Sub-Saharan African countries are highly vulnerable to global food prices, with the pass-through from global to local food prices estimated close to unity for highly imported staples. On the domestic side, staple food price inflation is lower in countries with greater local production and among products with lower consumption shares. Additionally, adverse shocks such as natural disasters and wars bring 1.8 and 4 percent staple food price surges respectively beyond generalized price increases. Economic policy can lower food price inflation, as the strength of monetary policy and fiscal frameworks, the overall economic environment, and transport constraints in geographically challenged areas account for substantial cross-country differences in staple food prices.